Properties and growth of human bone marrow mesenchymal stromal cells cultivated in different media - Turnovcova, Karolina; Ruzickova, Katerina; Vanecek, Vaclav; Sykova, Eva; Jendelova, Pavla (Cytotherapy, 2009)
BACKGROUND AIMS: Human mesenchymal stromal cells (hMSC) are a promising tool for future clinical application, but their use requires rapid cell expansion in media suitable for clinical use. Therefore, we tested the influence of several culture media on colony formation, population doubling (PD) time, cell cycle and surface marker expression. METHODS: hMSC isolated from human bone marrow (BM) obtained from healthy donors were seeded and expanded in different culture media: alpha-minimum essential medium (MEM) supplemented with 2.5%, 5%, 10% or 20% fetal bovine serum (FBS), 5% or 10% human cord blood serum (hCBS), 5% or 10% human blood serum from AB adult donors (hABS), or mesenchymal stem cell growth medium (MSCGM). The number, diameter and total area of the colonies formed and PD time were determined, and the cell cycle and 16 surface markers were analyzed. RESULTS: Colony-forming efficiency was best in alpha-MEM/hCBS and alpha-MEM/hABS, good in MSCGM and worst in alpha-MEM/FBS. The shortest PD time was achieved in media enriched with human sera or MSCGM, while the time was increased in alpha-MEM/FBS. The largest proliferating fraction was seen in MSCGM followed by media enriched with human sera; the fraction was smallest in alpha-MEM/FBS. Staining for CD34, CD45, CD235a and CD271 was negative, while that for CD29, CD44, CD73, CD90, CD105 and human leukocyte antigen (HLA)-A, -B, -C was positive in all media tested. Media with human serum did not adversely affect the differentiation potential of hMSC, and differentiation into osteoblasts was enhanced. CONCLUSIONS: The choice of serum influences hMSC expansion and cell properties; alpha-MEM supplemented with hABS seems to be a promising candidate for clinical use.
Keywords: diferenciační antigeny; buňky kostní dřeně; buňky - růstové procesy; Antigens, CD; Stromal Cells; kultivační média speciální; lidé; Cell Culture Techniques; Colony-Forming Units Assay; Humans; Mesenchymal Stem Cells; Antigens, Differentiation; buněčná diferenciace; Cell Growth Processes; analýza kolonii tvořících jednotek; Culture Media, Conditioned; zvířata; buňky stromatu; buněčné kultury; mezenchymální kmenové buňky; Animals; Bone Marrow Cells; Cell Differentiation; CD antigeny